Moderner Muskelkult: Zur Sozialgeschichte des Bodybuildings - Kläber, Mischa (transcript, 2014)
Bodybuilding polarizes: in bodybuilders, some see crazy freaks instead of athletes. Others, on the other hand, are excited by these extreme muscle fetishists. Internally, bodybuilders see themselves as true, thoroughbred athletes; and beyond this, as artists, ascetics and heroes. By way of bodybuilding techniques, the body becomes an instrument of distinction - to the point of becoming a meaningful entity. But how should the development of bodybuilding be categorized against the backdrop of modernity? Mischa Kläber shows that the social history of bodybuilding - together with its spillover effect into other sports - is at least as fascinating as the bodies of its protagonists.